GALLERY WALKâS AND PICTURE AND PICTURE TOWARD THE MATHâS RESULT STUDY - Mawardini, Annisa; Prasetyo, Teguh; Widyaningsih, Hadida (DIDAKTIKA TAUHIDI: JURNAL PENDIDIKAN GURU SEKOLAH DASAR, 2018)
This research based on the fact that how low Mathâs result study is. That is why the researcher applied Gallery Walk and Picture and Picture method. The aim of this study is to figure out the influence of Gallery Walkâs method implementation and Picture and Picture toward the Mathâs result study. The method used was quasi experiment with the static group pretest-postest design. The population in this research was all the student of fifth grader in Pasirgaok 02 elementary school. This research used nonprobability sampling as the technique of sampling which consisted of the saturated sample from two classes experiment. This research used observation, test and questionnaire as the technique of collecting data. According to the analysis result, the average score of posttest class of experiment 1 was 69,5 and the experiment two was 74,8. The result of One Sample T-test was sig 0.00, thus, it was rejected since 0.00 < 0.05 which means the method of Gallery Walk influenced toward the result study of the student. There was a difference in both method through independent T test, sig (2-tailed) 0,05 which rejected to emphasize the difference. So that, there was an influence of Gallery Walkâs method implementation and Picture and Picture toward the Mathâs result studyof the fifth graders of Pasirgaok 02 elementary school.Keywords : Gallery Walk and Picture and Picture method, Mathâs result study